2012
DOI: 10.1038/nn.3128
|View full text |Cite
|
Sign up to set email alerts
|

A color-coding amacrine cell may provide a blue-Off signal in a mammalian retina

Abstract: Retinal amacrine cells are thought to lack chromatic or color–selective light responses and play only a minor role in color processing. We now show that a type of mammalian (Ictidomys tridecemlineatus) amacrine cell selectively carries a blue–On signal, which is received from a blue or short–wavelength sensitive (S–) cone On bipolar cell. This glycinergic inhibitory “S–cone amacrine cell” is ideally placed for driving “blue–Off” responses in downstream ganglion cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 19 publications
4
47
0
Order By: Relevance
“…This indicates that both types of response originate from the same S-cone bipolar cell. In the ground squirrel, a sign-inverting S-cone amacrine cell that receives input from S-cone bipolars and is able to provide glycinergic inhibitory input to downstream ganglion cells has been found (21,22). These cells may thus provide the substrate to form the S-cone OFF ganglion cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that both types of response originate from the same S-cone bipolar cell. In the ground squirrel, a sign-inverting S-cone amacrine cell that receives input from S-cone bipolars and is able to provide glycinergic inhibitory input to downstream ganglion cells has been found (21,22). These cells may thus provide the substrate to form the S-cone OFF ganglion cell.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the S-cone response to increments is faster than the response to decrements, but the latter response is even slower for older individuals. The slower response may be attributable to different retinal circuitry, possibly including mediation by an inhibitory amacrine cell synapse (21,22) and/or a slow, melanopsin-containing retinal ganglion cell (16).…”
mentioning
confidence: 99%
“…An ON-type S-cone bipolar cell with an M-cone surround makes synapses with a glycinergic amacrine cell that contacts ganglion cells: The amacrine cell is excited by blue light, but excitation of the amacrine cell inhibits the postsynaptic ganglion cells. Thus, the ON response is inverted to an OFF response and its color-opponent nature is preserved (Chen & Li 2012, Sher & DeVries 2012). The above mechanisms for conveying S-cone signals to ganglion cells are apparently complemented by OFF-type S-cone bipolar cells in some species (Klug et al 2003, Yin et al 2009, Mills et al 2014).…”
Section: Lateral Inhibition Modifies Signaling By Vertical Excitatorymentioning
confidence: 99%
“…Presumably, the sign of the S-cone input is inverted by transmission through a glycinergic inhibitory S-cone amacrine cell similar to those responsible for S-OFF inputs to ganglion cells that have been characterized in ground squirrels. 24,25 The 'blue-OFF' color opponency was discovered before it was recognized as the homolog to the ipRGCs identified in rodents and Dacey and Packer 26 originally named them the 'large sparse monostratified' cell and they suggested that they might be the S-OFF counterpart to the small bistratified cell and the retinal basis for S-OFF chromatically opponent cells recorded in the primate LGN. Indeed, ipRGCs may be the +Y-B cells originally observed by DeValois et al 20 in their LGN recordings; however, instead of being associated with the perception of yellow, these are the dawn-and dusk-detecting ganglion cells that primates inherited from their osteichthyoid ancestors.…”
Section: Synaptic Inputs That Introduce S-cone Signals Into the Retinmentioning
confidence: 99%